Dynamics of Polygamy: An Attempt to Find Common Ground from the Perspective of Maqasid Sharia and Human Rights - Elvira Dewi Br Ginting; Iwan Iwan (JURNAL AKTA, 2024)
This study aims to find the intersection between maqashid sharia and human rights in the practice of polygamy. Polygamy, or marriage with more than one partner at the same time, is an Islamic teaching that, in light of Maqashid al-Syariah, is permissible as long as it brings benefits, but on the other hand, human rights activists consider polygamy as a form of violation of human rights. This study uses a qualitative approach by analyzing religious texts, laws, and other sources to understand how Maqashid Shariah can be applied in the context of polygamy. The results show that, while polygamy may be permissible in certain contexts, its practice must be aligned with the objectives of Maqashid Sharia, namely creating justice, welfare, and happiness for all parties involved. From a human rights perspective, there is no single article that discusses polygamy, but as seen from the Universal Declaration of Human Rights and the Convention on the Elimination of All Forms of Discrimination against Women, although Article 16 is interpreted as not allowing polygamy; Article 18 allows polygamy but with strict conditions, namely being fair or adjusted to the rules of each religion. This research provides new insights into how Islamic principles can be used to guide the practice of polygamy and emphasizes the importance of considering social needs so that it does not conflict with human rights.